Large‐scale pathogenicity prediction analysis of cancer‐associated kinase mutations reveals variability in sensitivity and specificity of computational methods - Sravani Akula; Sai Charitha Mullaguri; Niklas Max Melton; Archana Katta; Venkata Sai Giridhar Reddy Naga; Shyamson Kandula; Raj Kumar Pedada; Janakiraman Subramanian; Rama Krishna Kancha (Cancer Medicine, 2023)
Abstract Background Mutations in kinases are the most frequent genetic alterations in cancer; however, experimental evidence establishing their cancerous nature is available only for a small fraction of these mutants. Aims Predicition analysis of kinome mutations is the primary aim of this study. Further objective is to compare the performance of various softwares in pathogenicity prediction of kinase mutations. Materials and methods We employed a set of computational tools to predict the pathogenicity of over forty‐two thousand mutations and deposited the kinase‐wise data in Mendeley database (Estimated Pathogenicity of Kinase Mutants [EPKiMu]). Results Mutations are more likely to be drivers when being present in the kinase domain (vs. non‐kinase domain) and belonging to hotspot residues (vs. non‐hotspot residues). We identified that, while predictive tools have low specificity in general, PolyPhen‐2 had the best accuracy. Further efforts to combine all four tools by consensus, voting, or other simple methods did not significantly improve accuracy. Discussion The study provides a large dataset of kinase mutations along with their predicted pathogenicity that can be used as a training set for future studies. Furthermore, a comparative sensitivity and selectivity of commonly used computational tools is presented. Conclusion Primary‐structure‐based in silico tools identified more cancerous/deleterious mutations in the kinase domains and at the hot spot residues while having higher sensitivity than specificity in detecting deleterious mutations.